Acute renal tubular necrosis and death of mice orally infected with Escherichia coli strains that produce Shiga-like toxin type II. - Wadolkowski, E A (1990)
Escherichia coli O157:H7 strains have been implicated as etiologic agents in food-borne outbreaks of hemorrhagic colitis and the hemolytic-uremic syndrome. A prototype E. coli O157:H7 strain, designated 933, produces Shiga-like toxin I (SLT-I) and SLT-II and harbors a 60-MDa plasmid. In a previous study, streptomycin-treated mice were fed 933 together with a derivative cured of the 60-MDa plasmid (designated 933cu). Strain 933cu colonized poorly, but in approximately one-third of the animals, an isolate of 933cu was obtained from the feces that had regained the ability to colonize well. This isolate, designated 933cu-rev, killed all of the animals when fed alone to mice. In this investigation, two types of experiments were done to assess whether SLT-I, SLT-II, or both contributed to the death of mice fed 933cu-rev. (i) Mice were pretreated with monoclonal antibodies to SLT-I, SLT-II, SLT-I and SLT-II, or cholera toxin (as a control) before infection with 933cu-rev. (ii) Mice were fed either an E. coli K-12 strain carrying cloned SLT-I genes or the same K-12 strain carrying cloned SLT-II genes. The results of both types of experiments indicated that the deaths of the orally infected mice were due solely to SLT-II. Extensive histological and selected electron microscopic examinations of various tissues from the infected animals suggested that death was due to acute renal cortical tubular necrosis consistent with toxic renal damage. These data indicate a critical role for SLT-II, but not SLT-I, in renal damage associated with E. coli O157:H7 infection of streptomycin-treated mice.